Language barriers in healthcare delivery: a sociolinguistic case study of multilingual patients in Indonesian urban clinics - Maratusholikhah Nurtyas (Indonesian Journal of Medical Linguistics, 2026)
Background: Indonesia’s extreme linguistic diversity, combined with rapid urbanization, has intensified multilingual encounters in primary healthcare settings, raising concerns about communicative equity and patient safety. Objective: This study investigates how language barriers operate interactionally and institutionally in urban clinics by examining code-switching practices, sequential repair patterns, and language ideologies embedded in policy frameworks. Method: Using a qualitative multi-method design, this research analyzes 52 recorded consultations, 27 sociolinguistic interviews, and institutional documents through Interactional Sociolinguistics, Conversation Analysis, and Institutional Discourse Analysis. Results: The findings reveal that code-switching clusters in diagnostic and instructional phases, functioning as an alignment strategy under epistemic pressure. Sequential breakdown–repair patterns occur systematically in high-information segments, with minimal agreement tokens frequently masking incomplete comprehension. Institutional policies emphasizing standardized Indonesian and efficiency metrics generate alignment gaps that shift communicative responsibility onto patients and families. Implication: These results demonstrate that multilingualism operates simultaneously as communicative resource and structural vulnerability. Novelty: The novelty of this study lies in integrating micro-level sequential analysis with macro-level ideological critique, offering a layered explanatory model that reconceptualizes language barriers as structurally patterned phenomena within healthcare governance.